The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1128/aac.42.2.383
|View full text |Cite
|
Sign up to set email alerts
|

TXU (Anti-CD7)-Pokeweed Antiviral Protein as a Potent Inhibitor of Human Immunodeficiency Virus

Abstract: We have evaluated the clinical potential of TXU (anti-CD7)-pokeweed antiviral protein (PAP) immunoconjugate (TXU-PAP) as a new biotherapeutic anti-human immunodeficiency virus (anti-HIV) agent by evaluating its anti-HIV type 1 (anti-HIV-1) activity in vitro, as well as in a surrogate human peripheral blood lymphocyte-severe combined immunodeficient (Hu-PBL-SCID) mouse model of human AIDS. The present report documents in a side-by-side comparison the superior in vitro anti-HIV-1 activity of TXU-PAP compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The first report of a clinical pharmacokinetic study of TXU (anti-CD7)-PAP immunoconjugate in HIV-infected patients was reported with superior in vitro anti-HIV-1 activity of PAP compared with the activity of zidovudine (Uckun et al 1998). These observations may provide the basis for further investigation of PAP as a potential biotherapeutic agent for HIV patients.…”
Section: Future Prospectsmentioning
confidence: 91%
“…The first report of a clinical pharmacokinetic study of TXU (anti-CD7)-PAP immunoconjugate in HIV-infected patients was reported with superior in vitro anti-HIV-1 activity of PAP compared with the activity of zidovudine (Uckun et al 1998). These observations may provide the basis for further investigation of PAP as a potential biotherapeutic agent for HIV patients.…”
Section: Future Prospectsmentioning
confidence: 91%
“…Predictable activities. Compounds 3a to 3d were tested for RT inhibitory activity in cell-free assays using purified HIV RT (listed as IC 50 [rRT] in Table 2), as well as by in vitro assays of anti-HIV activity in human T-cell leukemia virus IIIB (HTLV-IIIB)-infected PBMNC (22,47,49) Table 2). Compound 3a, which showed the lowest activity and the worst interaction scores, inhibited rRT in two independent experiments with IC 50 s of 38.…”
Section: Resultsmentioning
confidence: 99%
“…Normal human PBMNC from HIVnegative donors were cultured for 72 h in RPMI 1640 medium supplemented with 20% (vol/vol) heat-inactivated fetal bovine serum, 3% interleukin-2, 2 mM L-glutamine, 25 mM HEPES, 2-g/liter NaHCO 3 , 50-g/ml gentamicin, and 4g/ml phytohemagglutinin prior to exposure to HIV-1 at a multiplicity of infection of 0.1 during a 1-h adsorption period at 37°C in a humidified 5% CO 2 atmosphere. Subsequently, cells were cultured in 96-well microtiter plates (100 l/ well; 2 ϫ 10 6 cells/ml, triplicate wells) in the presence of various inhibitor concentrations, and aliquots of culture supernatants were removed from the wells on day 7 after infection for antigen p24 enzyme immunoassays (EIA), as previously described (22,47,49). The applied p24 EIA was the unmodified kinetic assay commercially available from Coulter Corporation/Immunotech, Inc. (Westbrooke, Maine), which utilizes a murine monoclonal antibody to HIV core protein used to coat microwell strips to which the antigen present in the test culture supernatant samples binds.…”
Section: Construction Of the Nni Composite Binding Pocketmentioning
confidence: 99%
“…The IC 50 values were determined using the Statview statistics program (SAS Institute, San Francisco, CA, USA). In parallel, the effects of various treatments on cell viability were also examined as previously described [36]. In brief, nonin-fected PBMC were treated with each compound for 5 days under identical experimental conditions.…”
Section: Antiviral Susceptibility Assaysmentioning
confidence: 99%